Quilcapampa : A Wari Enclave in Southern Peru - Bautista, Stefanie L.; Yepez Álvarez, Willy, 1969-; Jennings, Justin (Book collections on Project MUSE., 2021)
"Analyzing evidence from the site of Quilcapampa in the Sihuas Valley of Southern Peru, contributors to this volume discuss the ninth-century settlement's relationship to the broader Wari empire and reimagine the empire's role in the widespread changes of the Andean Middle Horizon period"--